Effects of Paranosema locustae (Microsporidia) on the development and morphological phase transformation of Locusta migratoria (Orthoptera: Acrididae) through modulation of the neurotransmitter taurine - Ao-mei LI; Yue YIN; Yu-xin ZHANG; Liu ZHANG; Kai-qi ZHANG; Jie SHEN; Shu-qian TAN; Wang-peng SHI (Journal of Integrative Agriculture, 2020)
Neurotransmitters are important in the maintenance of phase transformation of Locusta migratoria (Arthropoda: Orthoptera). Here, the effects of the entomopathogen Paranosema locustae on the neurotransmitter taurine in migratory locusts were studied using biochemical methods. After inoculation with P. locustae, the taurine content of infected locusts significantly declined, but F/C values (ratio between the length of hind femur and the width of the head of locust) increased significantly, compared to healthy locusts. Meanwhile, F/C values of infected locusts that were injected with 2 µg of taurine showed no significant differences from those of healthy locusts, demonstrating that supplemental taurine inhibited the changes in morphological phase caused by P. locustae. Paranosema locustae infection also caused longer developmental durations and lower body weights of locusts, but these changes were unaffected after injection with taurine. These results provided new insights into the mechanisms by which microsporidian parasites affected their locust hosts.